PELATIHAN TOEFL-LIKE DENGAN MEDIA E-LEARNING BAGI PESERTA DIDIK DI SMAN 5 MADIUN - Priska Meilasari; Christina Maya Iriana Sari; Rr. Arielia Yustisiana (LPPM, Universitas Katolik Widya Mandala Surabaya, 2022)
TOEFL which stands for Test of English as a Foreign Language is a test used to measure the English proficiency of those who are non-native English language speakers. This test is usually becoming one of the requirements to enrol on domestic and foreign universities and apply to the state-owned enterprise (BUMN) and to some other companies. SMAN 5 Madiun has not given any TOEFL introduction lessons to its students. This program aimed at providing the participants with the ability to solve every question in TOEFL. This society service program was done through e-learning due to the covid-19 pandemic's unable us to have offline meetings. The methods used in this program are demonstration, exercising, and lecturing. The evaluation done by comparing the result of pre and post-tests showed that there is a significant increase in participants’ ability to solve the TOEFL questions.